2018
DOI: 10.1080/20469047.2018.1471381
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of intravenous immunoglobulin resistance and coronary artery aneurysm in patients with Kawasaki disease

Abstract: KD patients with reduced mean haemoglobin, increased AST level, increased neutrophil-to-lymphocyte ratio and reduced platelet count should be considered for conjunctive therapy such as a corticosteroid in combination with standard treatment. Duration of fever ≥8 days and platelet count ≥550 × 10/L were predictors of CAA. To prevent cardiovascular complications, patients should be treated promptly after KD has been diagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 26 publications
6
23
0
2
Order By: Relevance
“…Previous frequently reported risk factors for CAL, such as a higher platelet level, 27 , 28 a lower albumin level, 28 , 29 male sex, 6 , 28 30 IVIG resistance 6 , 29 , 31 and receiving initial IVIG beyond 10 days, 6 , 27 , 28 , 32 were also demonstrated in our findings. As for incomplete KD, study results were contradictory even in multivariate analyses.…”
Section: Discussionsupporting
confidence: 84%
“…Previous frequently reported risk factors for CAL, such as a higher platelet level, 27 , 28 a lower albumin level, 28 , 29 male sex, 6 , 28 30 IVIG resistance 6 , 29 , 31 and receiving initial IVIG beyond 10 days, 6 , 27 , 28 , 32 were also demonstrated in our findings. As for incomplete KD, study results were contradictory even in multivariate analyses.…”
Section: Discussionsupporting
confidence: 84%
“…The initial incidence of CALs judged by absolute diameter was 68% in IVIG-resistant group and 47% in IVIG-responsive group in this study. The initial CALs incidence in IVIG-resistant group was close to Han’s study 23 and was much higher than Chantasiriwan’s study 24 , but the incidences in IVIG-responsive groups were similar to theirs.…”
Section: Discussionsupporting
confidence: 65%
“…They speculated that, patients who were earlier diagnosed and treated were probably sicker and had greater inflammation. However, Chantashiriwan et al 24 reported duration of fever ≥ 8 days before IVIG as a predictor of coronary artery aneurism, similar with our results. Also, Gulhan et al 22 suggested administrating initial IVIG treatment within 7 days of illness to prevent cardiac complications.…”
Section: Discussionsupporting
confidence: 92%